Busy academics share less: the impact of professional and family roles on academic withholding behaviour. Issue 4 (3rd April 2022) - Defazio, Daniela; Kolympiris, Christos; Perkmann, Markus; Salter, Ammon
ABSTRACT: Although academics are increasingly expected to share their research data and materials with other academics, many appear reluctant to do so. While extant research emphasises commercial involvement and peer influence as determinants of withholding behaviour, we hypothesise that the volume of competing commitments plays an important role in preventing academics from sharing. Using rich, multi-source data on 876 academics at a large research university, we explore how withholding behaviour is related to the breadth of professional and family roles. We find that academics engaged in more activities, including research, teaching and commercialisation, and with more young children, are more likely than their colleagues to withhold research data and materials from their previously published research. We explore the implications of these findings for scientific production and exchange, and for academics' workloads.